Third Summit of the Americas. Declaration of the city of Quebec, April 22, 2001 - de los Estados Americanos, Organización (2016)
Following is the Joint Statement issued by the 34 Heads of State and Government, in Quebec City, Canada on April 22, 2001: We, the democratically elected heads of State and Government of the Americas, gathered in the city of Quebec in our Third Summit, we renew our commitment to hemispheric integration and national and collective responsibility in order to improve the economic well-being and security of our peoples. We have adopted an Action Plan to strengthen representative democracy, promote efficient governance and protect human rights and fundamental freedoms. We seek to create greater prosperity and increase economic opportunities and, at the same time, promote social justice and develop the human potential. We reiterate our firm commitment and adherence to the principles and purposes of the Charters of the United Nations and of the Organization of American States (OAS).